Molecular dynamics-guided insight into the adsorption–inhibition mechanism for controlling ice growth/melt of antifreeze protein type IV mutant from longhorn sculpin fish - Eskandari, Azadeh; Leow, Thean Chor; Abdul Rahman, Mohd Basyaruddin; Oslan, Siti Nurbaya (Springer Science and Business Media Deutschland GmbH, 2024)
Antifreeze proteins (AFPs) represent a distinctive class of proteins that exist in organisms thriving in sub-zero conditions and act as an inhibitor of ice growth by binding to the ice interfaces. The melting or growing inhibition characterization can explain the adsorption–inhibition mechanism. This mechanism occurred within the thermal hysteresis activity of AFPs and is not amenable to measure experimentally. AFPIV is a newly discovered type of AFPs that exhibit remarkably low activity in inhibiting ice recrystallization. Herein, the novel mutation of AFPIV has been developed through the incorporation of afp1m peptide fused to the AFPIV’s third helix with a newly designed linker. The bioinformatics tools were employed for verification purposes to evaluate and analyze the model. The main focus of the present study pertains to the ice growth inhibition and Kelvin effect associated with the AFPIV mutant (AFP1mc) in comparison with AFPIV at different temperatures. The investigation revealed that in AFP1mc the rate of ice growth in the surrounding area experiences a significant reduction regarding the ice depression point as dictated by the Gibbs–Thomson effect. Moreover, it can be deduced that above the equilibrium melting point, ice melting is inhibited by the formation of the concave ice/water while, below that temperature, the ice growth inhibition observed through the ice water convex formation; however, this mechanism exhibits greater strength in AFP1mc owing to its superior affinity toward ice interaction. These findings provide evidence that the activity of AFP1mc is much higher than the original AFPIV, rendering it competent for additional experimental investigations and practical deployment in AFP contexts. © The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.